طبيعة الأزمة في الدولة الليبية وتأثير العوامل الداخلية والخارجية في إدارة الأزمات - فطيس, نجاة عبد السلام (مجلة الاصالة, 2024)
طبيعة الأزمة في الدولة الليبية وتأثير العوامل الداخلية والخارجية في إدارة الأزمات